Pengaruh Self Confidence Terhadap Kemampuan Komunikasi Matematis Siswa - Daulay, Leni Agustina (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2024)
The aim of this research is to determine the effect of self confidence on the mathematical communication skills of class VII at MTs Swasta Atu Lintang Takengon. This research was conducted in clas VII of the MTs Swasta Atu Lintang Takengon. This type research is ex post facto. The population of this research is all students in class VII of MTs Swasta Atu Lintang Takengon for the 2019/2020 academic year with total 20 students. The sample used was a saturated sample of total sampling. Data collection were questionnaires and tests. The data analysis techniques in this research is inferential statistical analysis with partial and multiple analysis as well as simple and multiple linier regression. The result of of data analysis show that there is an influence of self confidence on students’ mathematical communication skills.